Use of gamma rays to produce Echeveria sp. mutants to boost the future profit of the national producer - Quesada-Cordero, Girlany (2025)
Radioinduced mutagenesis is a powerful tool for enhancing genetic variability in plants, enabling the induction of desired traits, absent in nature or lost through evolution and breeding. This study aimed to generate mutant lines of Echeveria sp. using gamma rays, expanding the variety of succulents available in Costa Rica. A disinfection treatment using 20 min of incubation in NaOCl resulted in 46.9 % aseptic explants. The medium containing 50 % MS salts and 6 g.L-1 of gelling agent proved to be the most effective for explant multiplication and hyperhydricity reduction. Leaves from Echeveria sp. vitroplants were exposed to gamma radiation doses of 0, 20, 40, 60, 80 and 100 Gy. The LD50 for vitroplant leaves was determined to be 23.16 Gy. Irradiated explants were subcultured in multiplication medium to promote sprouting and, after six subcultures, successfully acclimatized in greenhouse conditions. The established irradiation and micropropagation protocols proved to be effective for mutation induction in Echeveria sp., offering an innovative resource for developing new ornamental varieties and supporting their adoption by succulent producers.